1981
DOI: 10.1002/j.2164-4918.1981.tb00639.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Psychology: An Answer to Occupational Mental Health

Abstract: Corporate planners acknowledge that productivity is directly related to employee mental health. This recognition is reflected by the recent upsurge of corporate in‐house, human resource programs. Although their latent function may be economic rather than humanitarian, these programs nevertheless provide psychological assistance for problems considered to be normal episodes of human development. Counseling psychologists may be the best equipped to work with a corporate clientele because, unlike the clinician, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1994
1994

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Employees' psychological health and sense of wellbeing are also related to their perceptions of whether or not anyone listens to them; these perceptions, in turn, have a direct influence on workers' productivity [1,51]. Campbell's [52] study of women supports this hypothesis.…”
Section: Relationship Concernsmentioning
confidence: 99%
“…Employees' psychological health and sense of wellbeing are also related to their perceptions of whether or not anyone listens to them; these perceptions, in turn, have a direct influence on workers' productivity [1,51]. Campbell's [52] study of women supports this hypothesis.…”
Section: Relationship Concernsmentioning
confidence: 99%
“…Leonards (1981 ) has spoken of appropriateness of counselling psychologists becoming involved in industry because of their emphasis on working with healthy personalities. Leonards has suggested that among the roles of such persons would be counselling for resolution of mid-career issues, for retirement planning, and for specific career development concerns.…”
Section: Employmentmentioning
confidence: 99%